ALLOGENEIC TRANSPLANTATION FOR CHRONIC LYMPHOCYTIC LEUKEMIA - Luca Laurenti; Michela Tarnani; Patrizia Chiusolo; Federica Sorà; Simona Sica (Mediterranean Journal of Hematology and Infectious Diseases)
Even if Chronic lymphocytic leukemia (CLL) often has an indolent behavior with good responsiveness to cytoreductive treatment, about 20% of the patients, so called "poor-risk" patients, show an aggressive course and die within a few years despite early intensive therapies. Criteria for poor-risk disease according to the European Bone Marrow Transplantation (EBMT) CLL Transplant Consensus are: purine analogue refractoriness, early relapse after purine analogue combination therapy, CLL with p53 lesion requiring treatment.